Expression analysis of three SERK-like genes in barley under abiotic and biotic stresses. Issue 1 (1st January 2017) - Li, Yingbo; Liu, Chenghong; Guo, Guimei; He, Ting; Chen, Zhiwei; Gao, Runhong; Xu, Hongwei; Faheem, Muhammad; Lu, Ruiju; Huang, Jianhua
ABSTRACT: Somatic embryogenesis receptor-like kinases (SERKs), a subfamily of receptor-like kinases, showed important roles in plant response to abiotic and biotic stresses in addition to embryogenesis and organogenesis in numerous plant species. In the present study, three orthologs of SERK genes ( HvSERK1/2/3 ) were isolated from barley, and their expression patterns during in vitro culture of microspores as well as their responses to different stresses including salinity and powdery mildew were characterized. Sequence analysis suggested that three HvSERK genes were highly conserved in the grass family. Subcellular localization showed the HvSERK1 protein located on the plasma membrane. The HvSERK1 transcript was up-regulated during the microspore culture period, suggesting its roles in microspore embryogenesis. HvSERK1 and HvSERK3 showed the highest expression level in the leaves; however no difference was detected for HvSERK2 expression in different plants' tissues. Under salt stress, all three HvSERK genes were quickly induced in microspore-derived embryogenic calli, whereas only HvSERK1 was up-regulated in the roots of barley seedlings. Moreover, only HvSERK2 was induced in the barley leaves upon powdery mildew inoculation. These results suggest that barley SERK genes may participate in barley microspores' development and plant response toward salt and fungal stress, and the function of them has some evolutionary changes.